Costs and benefits of in-company vocational training - Beicht, Ursula [Verfasser]; Herget, Hermann [Verfasser]; Walden, Günter [Verfasser] (My University, 2007)
"In-company vocational education and training activities are not an end in themselves. In fact, they should bring about concrete benefits for the company. Vocational training can therefore be seen as an investment which has to yield a worthwhile return on costs in the long term. In a study by the Federal Institute for Vocational Education and Training (BIBB), a representative survey was conducted of some 2,500 companies involved in vocational training in the year 2001, in order to analyse the costs and benefits of training. It found that companies which directly provide in-company vocational training reap benefits on a substantial scale." (BIBB)
Erstveröffentlichung der englischen Version des Artikels in: BWP Special Edition 2005, S. 38-40
Keywords: S 4 Kosten & Finanzierung; S 1.3.1 Ausbildung im Dualen System; T 1.1 Empirische Berufsbildungsforschung; Kosten-Nutzen-Analyse; Betriebliche Berufsausbildung; Ausbildungskosten; Ausbildungsertrag